2019
DOI: 10.4081/idr.2019.7925
|View full text |Cite
|
Sign up to set email alerts
|

Strength Training Improves Body Composition, Muscle Strength and Increases CD4+ T Lymphocyte Levels in People Living with HIV/AIDS

Abstract: The establishment of physical training programs for people living with HIV/AIDS (PLWHA) has several benefits. The study aimed to analyze the effect of resistance training using prediction of intensity by subjective perception of effort (SPE) on body composition, muscle strength, and TCD4+ lymphocyte levels in PLWHA. This a randomized controlled trial study. Participants (11 men and 8 women), were divided in two groups: exercise group (EG) and control group (CG). The EG was submitted to 12 weeks of a resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
0
14
0
6
Order By: Relevance
“…These results reinforce the need for better nutritional monitoring, particularly in those patients with HIV, who also present chronic diseases like DM. In addition to nutritional care, it is important to note that properly monitored exercise programs are able to preserve muscle mass, improve body composition, as well as increase the number of CD4+T cells, which contributes to improving the quality of life in the population living with HIV/AIDS 55,56 .…”
Section: Resultsmentioning
confidence: 99%
“…These results reinforce the need for better nutritional monitoring, particularly in those patients with HIV, who also present chronic diseases like DM. In addition to nutritional care, it is important to note that properly monitored exercise programs are able to preserve muscle mass, improve body composition, as well as increase the number of CD4+T cells, which contributes to improving the quality of life in the population living with HIV/AIDS 55,56 .…”
Section: Resultsmentioning
confidence: 99%
“…Promotion of healthy lifestyles have thus become a priority for PLH under antiretroviral therapy (ART) as part of more comprehensive care approaches that include health promotion and engagement in physical activity (PA) [5,6]. In fact, there is evidence that combined resistance and aerobic training improve body composition, increase muscular strength, and reduce blood cholesterol of PLH [7][8][9]. In addition, training leads to increased cardiorespiratory fitness and flexibility of these patients [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, resistance exercise (RE) has been identified as a promising strategy to combat the damage caused by HIV in several health parameters, such as glycemic control, 19 blood pressure 20 and body composition. 21 However it is still unclear whether RE is able to modulate cognitive function in this population. In apparently healthy people, preliminary evidence has shown that chronic or acute resistance exercise induces an improvement in cognitive function, 15,[22][23][24] with the duration of the session (between 45 and 60 minutes) and the intensity (moderate or vigorous), appearing as variables that seem to moderate these changes.…”
Section: Introductionmentioning
confidence: 99%